Seychelles : Technical Assistance Report-External Sector Statistics. (IMF Staff Country Reports; Country Report, 2022)
A remote external sector statistics (ESS) technical assistance (TA) was provided to the Central Bank of Seychelles (CBS) during October 4-13, 2021. The main objectives of the mission were to (i) assist the authorities in improving the quality of ESS by focusing on actions undertaken by the CBS for collecting data from corporate service providers (CSPs) and their inclusion in the balance of payments and international investment position (IIP) statistics; (ii) assess the data reported by the CSPs and their fit into the ESS framework; (iii) prepare the basis for Seychelles' participation in the IMF's survey "Resident Special Purpose Entities: Cross Border Flows and Positions) (IMF's SPEs Survey); and (iv) review and assess the adequacy of estimated travel services.